Selenium bioaccesibility after in vitro digestion/fermentation of foods differs in adults and children. - García-Conde, Úrsula; Navarro-Alarcón, Miguel; Navajas Porras, Beatriz; Hinojosa-Nogueira, Daniel; Delgado-Osorio, Adriana; Navarro-Moreno, Miguel; Pérez-Burillo, Sergio; Pastoriza, Silvia; Douros, Konstantinos; Rufián-Henares, José Ángel (Elsevier, 2024)
Selenium (Se) as essential element regulates the immune, endocrine, reproductive and neurological systems through selenoproteins. More important than its content, is the fraction available to be absorbed (bioaccesibility) to exert its important metabolic functions. The objective of this study was to determine the bioaccessibility of Se (Se-BA) in multiple foods by an in vitro digestion/fermentation method. Samples were subjected to homemade culinary techniques and fermented with feces from healthy adults (HE-AD), and healthy (HE-CH) and unhealthy children (with gluten related disorders, GRD-CH; obesity, OB-CH; or allergy/intolerance to cow’s milk proteins, AICM-CH). Se-BA varied largely among samples depending on their vegetal/animal origin, category and type of food. Animal-vs. plant-based foods have higher mean Se concentration and total Se-BA (82.5(±97.5) and 93.6 (±8.58) vs. 44.3(±55.6) μg/kg and 77.7(±20.4)%, respectively). In plant-based foods, higher Se-BA values were found in the large intestine (41.0(±25.7) vs. 30.1(±26.7%) in animal-base foods). In comparison to raw foods, the cooking techniques of vegetal- and animal-based foods grouped by heating in liquid media (frying-boiling) or hot air (roasting-grilling) decrease Se-BA in the small intestine (42.5(±27.0) vs. 34.8(±25.1) and 34.0(±24.3), and 75.9(±38.0) vs. 52.4(±28.9) and 71.3(±24.8)%, respectively), while it is increased in the large intestine (36.6(±28.5) vs. 41.3(±24.9) and 44.2(±23.6), and 19.9(±30.4) vs. 39.9(±26.0) and 23.4(±22.7)%, respectively). The higher Se-BA levels in the large intestine found in HE-CH (42.1 (±26.5) vs. HE-AD (35.2(±27.1) and unhealthy children (GRD-CH and OB-CH; 38.0(±24.6) and 35.8(±28.1)%, respectively) could be related to greater demands on growth and specific fermentative microbiota.
Keywords: Selenio; Alimentos; Biodisponibilidad; Intestinos; Adultos; Niños; Selenium; Foods; Bioaccessibility; Small intestine; Large intestine; Adults; Children; Culinary techniques